Correction of Channel Imbalance for MIMO SAR Using Stepped-Frequency Chirps - Xiulian Luo; Yunkai Deng; Robert Wang; Lei Guo; Mingjiang Wang (International Journal of Antennas and Propagation)
To simultaneously achieve two-dimensional high resolution and wide swath in synthetic aperture radar (SAR), azimuth MIMO structure combined with stepped-frequency chirp signals was developed via splitting the antenna into N subapertures. During transmitting each subaperture transmits a chirp pulse at a different carrier frequency, while during receiving every subaperture receives the N scattered pulses at the same time. Separating the N scattered pulses received by each subaperture and downlinking them to the ground yield N2 different signal paths. Due to the dedicated network in the SAR system, the channel imbalance is inevitable. To correct the channel imbalance, this paper presents an external calibration method, where the channel characteristics are estimated from the peak value of a strong point target for each channel. Simulation and real raw data experiments are performed to validate the proposed method.